How Consumer Ethnocentrism Influences Purchase Intention of Local Products in Cambodia: Insights from the Extended Theory of Planned Behavior - Chhayna Cheng (UTSAHA: Journal of Entrepreneurship, 2026)
Understanding the factors that influence consumers’ decisions to purchase local products is crucial for promoting sustainable economic growth in developing countries. This study addresses the gap in empirical research by examining how consumer ethnocentrism affects purchasing behavior toward local products in Cambodia through the lens of the extended Theory of Planned Behavior (TPB). Using a quantitative approach, data were collected from 500 fourth-year undergraduates across various faculties at BELTEI International University via structured questionnaires and analyzed using Excel and SPSS. The results reveal that consumer ethnocentrism significantly and positively influences purchase intention (β=0.605, p<0.001) and affects the TPB components—attitude, subjective norm, and perceived behavioral control. Attitude (β=0.230, p<0.001), subjective norm (β=0.126, p<0.01), and perceived behavioral control (β=0.525, p<0.001) each positively contribute to purchase intention, explaining 66.0% of its variance. These findings underscore the vital role of consumer ethnocentrism in encouraging local product purchases and validate the extended TPB as an effective framework for understanding consumer behavior in Cambodia. The study provides valuable insights for policymakers, producers, consumers, and researchers to develop strategies that enhance support for local products and promote economic sustainability. Future research is recommended to further explore consumer ethnocentrism within the extended TPB framework across diverse sectors and cultural contexts.